Evaluation of accessibility at Lollapalooza Chile (2023–2024): A quantitative analysis of the experience of people with disabilities attending the festival - Allende Vilches, Constanza; Quidel Caro, Mauricio; Zapata-Campos, Felipe; Cuevas Soto, Antonia (Relatos Journal, 2025)
Accessibility at large-scale music events (LME) is key to the cultural citizenship of people with disabilities (PwD), yet quantitative, context-specific evidence in Latin America is scarce. Objective. To describe perceived accessibility and inclusion among PwD at Lollapalooza Chile (2023–2024) and compare results by edition and disability group. Methods. Quantitative phase of a mixed-methods study; cross-sectional on-site survey using intercept sampling in adapted areas and, when observable, at other points. Convenience samples: 2023 (n=68) and 2024 (n=95). Instrument included 1–7 rating scales and open-ended questions. We computed descriptives and two indices: a General Accessibility Index (10 items) and a Services–Core Index (10 comparable items: P22, P23 harmonized, P25b, P26–P32). Comparisons 2023 vs. 2024 used Mann–Whitney U (Holm adjustment within item families); comparisons by disability type (Physical vs. Other) used Kruskal–Wallis. Complete-case analyses; no weights or imputation; α=0.05. Results. We analyzed 163 surveys. The General Index increased from 4.5 to 4.9 (p=0.026) and the Services–Core Index from 4.6 to 5.1 (p=0.039). After Holm adjustment, comparative items rating Lollapalooza against previous editions and other LMEs remained significant. No significant differences by disability group were found in either index. P24 and P25a were reported descriptively only due to low coverage/asymmetric measurement. Conclusions. From 2023 to 2024 there was a significant, broad-based improvement in perceived accessibility, consistent with operational adjustments by the festival; the lack of differences by disability type suggests a cross-cutting impact, to be interpreted cautiously given nonprobability sampling and possible underrepresentation of non-visible disabilities. We recommend institutionalizing co-design with PwD, strengthening accessible communication, and adopting verifiable standards for LMEs. The qualitative phase, to be published separately, will help triangulate perceived mechanisms of improvement.
Keywords: accessibility; people with disabilities; mass events; music festivals